KAJIAN HUKUM ISLAM TERHADAP UJARAN KEBENCIAN/HATE SPEECH DAN BATASAN KEBEBASAN BEREKSPRESI - Yayan Muhammad Royani (Jurnal Iqtisad, 2018)
ABSTRACTHate speech is a special term for criminal offenses such as hate expression, incitement, libel and defamation on behalf of race, ethnicity, religion, class or gender. That action is flare in public communication, especially in the Internet media. Although there have been various regulations governing, countermeasures against hate speech is not maximized. It could not be separated from the difficulty of determining the boundaries of hate speech with freedom of expression. This study aims to answer these problems in the perspective of Islamic law. The theory used is takzir and Maqasidu al-Syari’ah. The results of this study illustrate that the hate speech is a criminal offense punishable takzir and require a social approach in overcoming it. In the formulation of Islamic law, definition of hate speech is taken from the Korans argument that protect human rights in order to be limiting freedom of expression. Keywords: Speech, Hate, Law, Islam